Pytania wokół roli tożsamości w wychowaniu - Olbrycht, Katarzyna (Horyzonty Wychowania, 2017)
The text is an attempt to consider the questions connectedwith the role of identity in education. The author suggests a fewquestions – problems, presenting them in the light of the selectedtheoretical standpoints. Finally, she justifies the need for recognizingidentity in both theory and practice of education,emphasising the inevitability of an extended pedagogical reflectionin this field, as well as making specific anthropological-philosophicalassumptions. She also formulates several tasks connectedwith the educational activity aiming for the formation ofidentity. In conclusion, the author pays attention to the need forthe educators to deepen their own identity.